Deep impurity removal method for electrolytic aluminum overhaul slag leachate
Through graded grinding and multi-step impurity removal processes, the problems of high cost of overhauling electrolytic aluminum overhauling slag and difficult to remove impurities were successfully solved, achieving complete recovery of lithium elements and improving the performance of lithium batteries.
Patent Information
- Application Number
- CN202510152441.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
AI Technical Summary
The existing electrolytic aluminum overhaul slag removal methods are costly and difficult to effectively remove impurities such as fluorine, boron, calcium, magnesium, etc., which affects the electrochemical performance and safety of lithium batteries.
By performing graded grinding of electrolytic aluminum overhaul slag, adding strong acid to leach lithium element, then removing iron aluminum ions and calcium magnesium ions under weak acid and alkaline conditions, fluorine is removed using activated magnesium oxide, and deep impurity removal is carried out using adsorption resin and complexing agent. Finally, sodium phosphate is added and lithium reacted to obtain lithium phosphate precipitation.
The electrolytic aluminum overhaul slag leaching liquid is used to remove impurities such as fluorine, boron, calcium, magnesium, etc., ensuring the complete recycling of lithium elements, reducing the cost of impurities removal, and improving the electrochemical performance and safety of lithium batteries.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for deep impurity removal of electrolytic aluminum overhaul slag leaching liquid. Background Art
[0002] At present, in aluminum electrolysis production, in order to improve current efficiency and reduce energy consumption, in addition to adding aluminum fluoride and cryolite, some lithium-containing salts such as fluoride or chloride are usually added to improve the properties of the electrolyte. With the use of lithium-containing fluoride salts, lithium-containing aluminum electrolysis waste slag is produced, and its lithium content is 1% to 2.7% (in terms of Li + With the increase of current aluminum production and the increase of aluminum electrolysis waste year by year, how to reasonably recycle and utilize this part of lithium resources will become a major issue to alleviate the pressure of lithium use brought by the new energy industry, and also reduce the disposal cost of aluminum electrolysis overhaul slag. It can be seen that the synthesis of lithium battery positive electrode materials from overhaul slag is a very economical choice for reducing the cost of lithium batteries and the utilization of electrolytic aluminum waste. Among them, the overhaul slag is leached with sulfuric acid to obtain lithium sulfate leaching solution, and then carbonate or phosphate is used to precipitate lithium to obtain lithium carbonate or lithium phosphate for synthesizing lithium batteries. However, the overhaul slag has a complex composition, and the impurities in its lithium sulfate leaching solution include Na, K, F, Cl, B, Ca, Mg, Al, Fe, etc. Among these impurities, Na, K, Cl and other soluble impurities can be removed by solid-liquid separation and stirring in the lithium precipitation process. Fe and Al can be removed more thoroughly by adjusting the pH value of the leaching solution. F, B, Ca, and Mg are relatively difficult to remove and require deep impurity removal. And fluorine content (F - ) is one of the important indicators of battery-grade lithium carbonate. Excessive fluorine content will have a negative impact on the electrochemical performance and safety of the battery. The following are the specific requirements for fluorine content in battery-grade lithium carbonate and its impact: Battery-grade lithium carbonate has very strict requirements on fluorine content, which is usually controlled at the ppm level (parts per million). The requirement for fluorine content in battery-grade lithium carbonate is usually ≤10ppm, and high-end applications may require ≤5ppm or even lower. Excessive fluorine content will seriously affect the performance and safety of the battery, so the fluorine content needs to be controlled through strict raw material selection, process optimization and post-processing purification.
[0003] The existing invention patent with the publication number of CN112853120A discloses a method for deep defluorination of LiHCO3 solution recovered from waste lithium batteries. After defluorination, the fluorine content of the solution can be reduced to less than 5 mg / L. However, the defluorinator is a composite material made of aluminum oxide, butyl titanate, zirconium sulfate and nitrogen-containing compounds after acid activation. The material preparation is complicated and the cost is high. And the existing invention patent with the publication number of CN113582206A discloses a method for recovering and preparing crude lithium carbonate from battery material raffinate. After defluorination, the fluorine content of the solution can be reduced to less than 3 mg / L. The defluorinator is a zirconium-based defluorinator with a main content of ZrO2+TIO2≥33%. The defluorinator is complicated to prepare and the raw material cost is high. And the existing invention patent with the publication number of CN111533100A discloses a method for preparing battery-grade lithium phosphate, which uses a three-stage resin to remove impurities. After the impurities are removed, the content of F, B, Ca, and Mg is below 3 mg / L, but the resin cost of this method is high and a large amount of wastewater is generated. And the existing invention patent with the publication number of CN112250090A discloses a production method for deep defluorination of lithium sulfate solution. This method uses active magnesium hydroxide, magnesium oxide, magnesium sulfate, magnesium nitrate or magnesium chloride as a defluorinating agent, which can reduce the fluorine content of the solution to below 5 mg / L, but this method can only remove fluorine in the solution, and a certain amount of magnesium will remain after defluorination, which requires further impurity removal, thereby increasing cost investment. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution, aiming to solve the technical problem of high cost of impurity removal of electrolytic aluminum overhaul slag.
[0005] To achieve the above object, the present invention provides a method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution, the method comprising the following steps:
[0006] Step 1, subjecting electrolytic aluminum overhaul slag to graded grinding to obtain slag powder with a preset particle size;
[0007] Step 2, adding slag powder into pure water and mixing and stirring, then heating the water to 70-100° C., and finally adding strong acid to react for 2-4 hours to fully leach the lithium element, and filtering to obtain a crude electrolytic aluminum overhaul slag leaching solution and leaching slag, wherein the strong acid is one of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid, and the pH value of the solution after adding the strong acid is 2-2.5, and the leaching solution contains iron and aluminum ions;
[0008] Step 3: heating the crude electrolytic aluminum overhaul slag leaching solution obtained in step 2 to 50-70° C., then adding a preset amount of hydrogen peroxide to react, and adding a regulator to adjust the pH of the solution to 4-7, filtering to obtain a filtrate and iron-aluminum slag, wherein the regulator includes at least one of an alkaline salt and an alkaline oxide, and the filtrate contains calcium and magnesium ions;
[0009] Step 4, adding a strong alkali solution to the filtrate obtained in step 3 to adjust the pH to 10-11, adding a strong base weak acid salt to react, filtering to obtain a primary impurity removal liquid and part of the calcium and magnesium slag, wherein the primary impurity removal liquid contains fluorine, and the molar amount of the strong base weak acid salt is 100-120% of the total molar amount of calcium and magnesium ions;
[0010] Step 5, adding active magnesium oxide to the primary impurity removal liquid in step 4, stirring and reacting for a preset time at room temperature, so that the magnesium ions are hydrolyzed to form porous, highly dispersed, highly active hydroxides or hydrated oxides, and complexed with fluoride ions to form colloids or flocs, and filtered to obtain a secondary impurity removal liquid;
[0011] Step 6, subjecting the secondary impurity removal liquid to metal ion adsorption treatment using an adsorption resin to obtain a tertiary impurity removal liquid;
[0012] Step 7, adding a complexing agent for complexing with boron to the tertiary impurity removal solution, and adding a preset amount of sodium phosphate to obtain lithium phosphate and lithium precipitation mother liquor.
[0013] Optionally, in step 1, the overhaul slag graded grinding treatment is to first coarsely crush the overhaul slag in a crusher, and then grind it using a sealed sample making machine, and the D90 particle size of the slag powder obtained by the graded grinding treatment is less than or equal to 74 μm.
[0014] Optionally, in step 2, the mass volume ratio of slag powder to pure water is 1 g: (2-5) mL.
[0015] Optionally, in step 3, the molar amount of hydrogen peroxide is 1 to 5 times the molar amount of iron in the leachate.
[0016] Optionally, in step 3, the alkaline salt includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate and potassium carbonate; and the alkaline oxide includes at least one of calcium oxide and magnesium oxide.
[0017] Optionally, in step 4, the strong alkaline solution includes at least one of sodium hydroxide and potassium hydroxide, and the strong base weak acid salt includes at least one of sodium carbonate, sodium bicarbonate and potassium carbonate.
[0018] Optionally, in step 5, the mass of the activated magnesium oxide is 30 to 100 times the mass of fluorine in the primary impurity removal liquid.
[0019] Optionally, in step 6, the adsorption resin includes at least one of an aminophosphonic acid chelating resin, an iminodiacetic acid resin and a strongly acidic cation exchange resin.
[0020] Optionally, in step 7, the complexing agent includes one of N-methyl-D-glucamine, mannitol and glucose.
[0021] Optionally, in step 7, the molar amount of sodium phosphate added is (0.9-1.1) / 3 times the molar amount of lithium ions contained in the tertiary impurity removal solution.
[0022] Beneficial effects:
[0023] The present invention grinds the electrolytic aluminum overhaul slag into powder by graded grinding, and then adds a strong acid to effectively leach the main elements therein, especially the lithium element. The iron and aluminum ions are effectively removed under weakly acidic conditions, some calcium and magnesium ions are removed under alkaline conditions, active magnesium oxide is added to remove fluorine, and adsorption resin is used to adsorb and remove the remaining high-valent metal ions such as calcium and magnesium, and a complexing agent is added to remove boric acid, so that the remaining filtrate mainly contains lithium. Finally, sodium phosphate is added to react with lithium to obtain lithium phosphate precipitation, so that the entire impurity removal method does not cause lithium loss and does not introduce new impurities. It can be seen that the deep impurity removal method of the electrolytic aluminum overhaul slag leachate of the present invention can achieve deep removal of impurities such as fluorine, boron, calcium, and magnesium from the electrolytic aluminum overhaul slag leachate, and the entire impurity removal method does not cause lithium loss and does not introduce new impurities. In addition, the method does not require expensive equipment and reagents, and the process flow is simple, which reduces the cost of impurity removal. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a schematic flow chart of an embodiment of a method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution.
[0025] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0026] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0027] See also Figure 1 The present invention provides a schematic flow chart of a method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution, the method comprising the following steps:
[0028] Step 1: Grind the electrolytic aluminum overhaul slag in a graded manner to obtain slag powder with a preset particle size. Specifically, the overhaul slag graded grinding process is to firstly crush the overhaul slag in a crusher, and then grind it using a sealed sample making machine, so that the D90 particle size of the slag powder obtained by the graded grinding process is less than or equal to 74 μm. And the main elements in the slag powder include lithium, iron, aluminum, calcium, magnesium, fluorine, and boron.
[0029] Step 2, place the slag powder in a corresponding container and add pure water to mix and stir, then heat the water to 70~100℃, continue to add strong acid to react for 2~4h, so that the lithium element is fully leached, and filter to obtain the crude electrolytic aluminum overhaul slag leachate and leached slag. Among them, the water heating method is preferably water bath heating, and the added strong acid is one of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid, and the pH value of the solution is controlled to be 2~2.5 after adding the strong acid; preferably, the mass fraction of concentrated sulfuric acid is 98%, and the amount of sulfuric acid is 80~120% of the molar amount of all elements in the overhaul slag that can react with sulfuric acid (hereinafter referred to as the theoretical acid consumption molar amount). The control of the above leaching temperature, leaching time and sulfuric acid amount can ultimately ensure that the lithium element is fully leached, and further dissolve the iron, aluminum, calcium, magnesium, fluorine, boron and other elements in the original slag powder.
[0030] Step 3, heating the crude electrolytic aluminum overhaul slag leaching solution obtained in step 2 to 50-70° C., then adding a preset amount of hydrogen peroxide to react, and adding a regulator to adjust the pH of the solution to 4-7, and filtering to obtain a filtrate and iron-aluminum slag, wherein the regulator includes at least one of an alkaline salt and an alkaline oxide, and the filtrate contains calcium and magnesium ions.
[0031] Specifically, the crude electrolytic aluminum overhaul slag leachate contains iron and aluminum ions, and the molar amount of the added hydrogen peroxide is 1 to 5 times the molar amount of iron in the leachate, and then the pH value of the solution is adjusted by adding a regulator, the purpose of which is to neutralize the residual acid in the electrolytic aluminum overhaul slag leachate with alkaline salts and alkaline oxides, and react with iron ions and aluminum ions to generate iron hydroxide and aluminum hydroxide precipitates under weak acid conditions, that is, the reaction endpoint pH is controlled to be 4 to 7, and the pH is continued to be adjusted after the iron and aluminum precipitation is complete to carry out the operation of precipitating calcium and magnesium, so as to avoid the generated iron and aluminum precipitates from existing in the system for a long time to adsorb and take away lithium.
[0032] Preferably, the alkaline salt includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate and potassium carbonate; and the alkaline oxide includes at least one of calcium oxide and magnesium oxide.
[0033] Step 4, adding a strong alkali solution to the filtrate obtained in step 3 to adjust the pH to 10-11, adding a strong alkali acid salt to react, and filtering to obtain a primary impurity removal liquid and part of the calcium and magnesium slag.
[0034] Specifically, by adding a strong alkali solution to adjust the pH, and further adding a strong base weak acid salt to achieve the reaction with calcium and magnesium ions in the filtrate under alkaline conditions to generate magnesium hydroxide, calcium hydroxide, magnesium carbonate, and calcium carbonate precipitates. Preferably, the molar amount of the strong base weak acid salt added is 100-120% of the total molar amount of calcium and magnesium ions; more preferably, the strong alkali solution includes at least one of sodium hydroxide and potassium hydroxide, and the strong base weak acid salt includes at least one of sodium carbonate, sodium bicarbonate and potassium carbonate.
[0035] Step 5, adding active magnesium oxide to the primary impurity removal liquid in step 4, stirring and reacting for a preset time at room temperature, and filtering to obtain a secondary impurity removal liquid.
[0036] Specifically, the primary impurity removal liquid also contains fluorine, and fluorine and magnesium can form a precipitate that is insoluble in water. Then, by adding active magnesium oxide, active magnesium oxide has a large specific surface area and abundant surface active sites, which can effectively capture fluoride ions F in water through physical and chemical adsorption. - , and the hydroxyl -OH on the surface of the active magnesium oxide also forms a complex with the fluoride ions, further enhancing the defluorination effect, and some ions on the surface of the active magnesium oxide can be exchanged with the fluoride ions, further removing the fluoride ions, and then hydrolyzing through the magnesium ions, and generating porous, highly dispersed, highly active hydroxides or hydrated oxides, and complexing with the fluoride ions to form colloids or flocs, thereby co-precipitating. Preferably, the mass of the active magnesium oxide is 30 to 100 times the mass of fluorine in the primary impurity removal liquid.
[0037] Step 6, subjecting the secondary impurity removal liquid to metal ion adsorption treatment with an adsorption resin to obtain a tertiary impurity removal liquid. The adsorption resin comprises at least one of an aminophosphonic acid chelating resin, an iminodiacetic acid resin, and a strongly acidic cation exchange resin. The adsorption resin chelates with high-valent metal ions, thereby achieving the removal of high-valent metal ions such as calcium and magnesium in the solution.
[0038] Step 7, add a complexing agent for complexing with boron to the tertiary impurity removal solution, and add a preset amount of sodium phosphate to obtain lithium phosphate and lithium precipitation mother liquor. Wherein, the complexing agent includes one of N-methyl-D-glucosamine, mannitol and glucose, and sodium phosphate reacts with lithium to obtain lithium phosphate precipitation. Preferably, the molar amount of sodium phosphate added is (0.9~1.1) / 3 times the molar amount of lithium ions contained in the tertiary impurity removal solution, and the main components of the precipitation mother liquor are sodium sulfate and residual sodium phosphate solution. By controlling the amount of sodium phosphate added, most of the lithium in the lithium sulfate solution can be precipitated as lithium phosphate. And the complexing principle of the complexing agent and boron is that N-methyl-D-glucosamine reacts with boric acid in the solution to form a soluble complex, thereby increasing the molecular size, so that it will not be wrapped in lithium phosphate crystals in the subsequent lithium precipitation process, thereby achieving the effect of impurity removal. The boron content in the finally synthesized lithium phosphate is reduced to less than 0.01%.
[0039] Furthermore, in step 2, the mass volume ratio of slag powder to pure water is 1 g: (2-5) mL.
[0040] The present invention grinds the electrolytic aluminum overhaul slag into powder by graded grinding, and then adds a strong acid to effectively leach the main elements therein, especially the sufficient leaching of lithium elements, and effectively removes iron and aluminum ions under weak acidic conditions, removes part of calcium and magnesium ions under alkaline conditions, adds active magnesium oxide to remove fluorine, uses adsorption resin to adsorb and remove the remaining high-valent metal ions such as calcium and magnesium, and adds a complexing agent to remove boric acid, so that the remaining filtrate mainly contains lithium, and finally adds sodium phosphate to react with lithium to obtain lithium phosphate precipitation, so that the entire impurity removal method will not cause lithium loss and will not introduce new impurities. It can be seen that the deep impurity removal method of the electrolytic aluminum overhaul slag leachate of the present invention can achieve deep removal of impurities such as fluorine, boron, calcium, and magnesium from the electrolytic aluminum overhaul slag leachate, and the entire impurity removal method will not cause lithium loss and will not introduce new impurities.
[0041] Further, in order to better illustrate the process and effect of a method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution, the following is a detailed description through specific embodiments, the details are as follows:
[0042] Example 1
[0043] Step 1, weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing, and grind it with a sealed sample making machine for 2-5 minutes to obtain slag powder 1 with a particle size less than 200 mesh, the main chemical composition of which is shown in Table 1 below (elements are tested on a dry basis).
[0044] Table 1 - Mass percentage of main elements in slag powder
[0045] Step 2, take 100g of slag powder 1, add it to 200mL of purified water, heat it to 85°C, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2. Filter to obtain the crude electrolytic aluminum overhaul slag leaching liquid and leaching slag.
[0046] Step 3, the crude electrolytic aluminum overhaul slag leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, and calcium oxide is slowly added to adjust the pH to 6.5. The reaction time is 1 hour and the filtrate and iron-aluminum slag are obtained by filtering.
[0047] Step 4, adding sodium hydroxide to the filtrate to adjust the pH to 11, adding an appropriate amount of sodium carbonate to react for 1 hour, filtering to obtain a primary impurity removal liquid and most of the calcium and magnesium impurities. The chemical composition of the primary impurity removal liquid is shown in Table 2.
[0048] Table 2 - Concentration of main components of primary impurity removal liquid
[0049] Step 5, adding active magnesium oxide with 30 times the fluorine content to the primary impurity removal liquid in step 4, stirring and reacting at room temperature for 3 hours, filtering to obtain a secondary impurity removal liquid, the chemical composition of which is shown in Table 3.
[0050] Table 3 - Concentration of main components of secondary impurity removal liquid
[0051] Step 6: The secondary impurity removal liquid in step 5 is adsorbed and removed by using iminodiacetic acid resin to obtain a tertiary impurity removal liquid, the chemical composition of which is shown in Table 4.
[0052] Table 4 - Concentration of the main components of the three-time impurity removal solution
[0053] Step 7: Add N-methyl-D-glucamine to the three impurity removal solutions in step 6, stir evenly, add a theoretical amount of sodium phosphate to precipitate lithium, and obtain lithium phosphate and lithium precipitation mother liquor. The lithium phosphate is washed with water and acid to remove impurities, and its chemical composition is shown in Table 5.
[0054] Table 5 - Mass percentage of main elements of lithium phosphate
[0055] Example 2
[0056] Step 1: Weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing. Use a sealed sample making machine to grind it for 2-5 minutes until the particle size is less than 200 mesh slag powder 1. Its main chemical composition is as follows (elements are tested on a dry basis):
[0057] Step 2: Take 100g of slag powder 1, add it to 200mL of purified water, heat it to 70℃, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2.5. Filter to obtain the crude electrolytic aluminum overhaul slag leaching liquid and leaching slag.
[0058] Step 3: The crude electrolytic aluminum overhaul slag leaching solution is heated to 50°C, an appropriate amount of hydrogen peroxide is added, and calcium oxide and calcium carbonate are slowly added to adjust the pH to 4. The reaction time is 1 hour and the filtrate and iron-aluminum slag are obtained by filtering.
[0059] Step 4, add sodium hydroxide to the filtrate to adjust the pH to 10, add an appropriate amount of sodium carbonate to react for 1 hour, and filter to obtain a primary impurity removal liquid. The chemical composition of the primary impurity removal liquid is as follows:
[0060] Step 5: Add active magnesium oxide with 30 times the fluorine content to the primary impurity removal liquid in step 4, stir at room temperature for 3 hours, and filter to obtain a secondary impurity removal liquid, the chemical composition of which is as follows:
[0061] Step 6: The secondary impurity removal liquid in step 5 is adsorbed and removed by aminophosphonic acid chelating resin to obtain a tertiary impurity removal liquid, the chemical composition of which is as follows:
[0062] Step 7: Add N-methyl-D-glucamine to the three times impurity removal solution in step 6, stir evenly, add a theoretical amount of sodium phosphate to precipitate lithium, and obtain lithium phosphate and lithium precipitation mother liquor. The lithium phosphate is washed with water and acid to remove impurities, and its chemical composition is as follows:
[0063] Example 3
[0064] Step 1: Weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing. Use a sealed sample making machine to grind it for 2-5 minutes until the particle size is less than 200 mesh slag powder 1. Its main chemical composition is as follows (elements are tested on a dry basis):
[0065] Step 2: Take 100g of slag powder 1, add it to 200mL of purified water, heat it to 100℃ and stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2.5. Filter to obtain the crude electrolytic aluminum overhaul slag leaching liquid and leaching slag.
[0066] Step 3: The crude electrolytic aluminum overhaul slag leaching solution is heated to 70°C, an appropriate amount of hydrogen peroxide is added, and calcium oxide is slowly added to adjust the pH to 7. The reaction time is 1 hour and the filtrate and iron-aluminum slag are obtained by filtering.
[0067] Step 4, sodium hydroxide is added to the filtrate to adjust the pH to 11, an appropriate amount of sodium carbonate is added to react for 1 hour, and the primary impurity removal liquid is obtained by filtration. The chemical composition of the primary impurity removal liquid is as follows:
[0068] Step 5: Add active magnesium oxide with 30 times the fluorine content to the primary impurity removal liquid in step 4, stir at room temperature for 3 hours, and filter to obtain a secondary impurity removal liquid, the chemical composition of which is as follows:
[0069] Step 6: The secondary impurity removal liquid in step 5 is adsorbed and removed by a strong acid cation exchange resin (e.g., 732 cation exchange resin, D072 macroporous strong acid styrene cation exchange resin, 001×8 strong acid styrene cation exchange resin, etc.) to obtain a tertiary impurity removal liquid, the chemical composition of which is as follows:
[0070] Step 7: Add N-methyl-D-glucamine to the three times impurity removal solution in step 6, stir evenly, add a theoretical amount of sodium phosphate to precipitate lithium, and obtain lithium phosphate and lithium precipitation mother liquor. The lithium phosphate is washed with water and acid to remove impurities, and its chemical composition is as follows:
[0071] Comparative Example 1
[0072] Step 1: Weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing. Use a sealed sample making machine to grind it for 2-5 minutes until the particle size is less than 200 mesh slag powder 1. Its main chemical composition is as follows (elements are tested on a dry basis):
[0073] Step 2: Take 100g of slag powder 1, add it to 200mL of purified water, heat it to 85℃, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2-2.5. Filter to obtain the crude electrolytic aluminum overhaul slag leaching liquid and leaching slag.
[0074] Step 3: The crude electrolytic aluminum overhaul slag leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, and calcium oxide is slowly added to adjust the pH to 6.5. The reaction time is 1 hour, and the filtrate and iron-aluminum slag are obtained by filtering. Sodium hydroxide is added to the filtrate to adjust the pH to 10-11, and an appropriate amount of sodium carbonate is added to react for 1 hour, and the primary impurity removal liquid is obtained by filtering. The chemical composition of the primary impurity removal liquid is as follows:
[0075] Step 4: Add a theoretical amount of sodium phosphate to the primary impurity removal solution in step 3 to precipitate lithium, to obtain lithium phosphate and lithium precipitation mother liquor. The lithium phosphate is washed with water and acid to remove impurities, and its chemical composition is as follows:
[0076] As can be seen from the above, Comparative Example 1 does not involve further filtration of fluorine, and the remaining metal ions are not further removed, so that the final lithium phosphate still contains a high proportion of impurities. However, by using the deep impurity removal method of the present invention, the boron content in the final lithium phosphate in the above Examples 1-3 is reduced to less than 0.01%, and substantially no impurities such as fluorine, calcium, and magnesium are contained.
[0077] Comparative Example 2
[0078] Step 1: Weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing. Use a sealed sample making machine to grind it for 2-5 minutes until the particle size is less than 200 mesh slag powder 1. Its main chemical composition is as follows (elements are tested on a dry basis):
[0079] Step 2: Take 100g of slag powder 1, add it to 200mL of purified water, heat it to 85℃, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2-2.5. Filter to obtain the crude electrolytic aluminum overhaul slag leaching liquid and leaching slag.
[0080] Step 3: The crude electrolytic aluminum overhaul slag leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, and calcium oxide is slowly added to adjust the pH to 6.5. The reaction time is 1 hour, and the primary impurity removal liquid is obtained by filtration. The chemical composition of the primary impurity removal liquid is as follows:
[0081] Step 4: Add the theoretical amount of sodium phosphate to the primary impurity removal solution in step 3 to precipitate lithium, to obtain lithium phosphate and lithium precipitation mother liquor. The lithium phosphate is washed with water and acid to remove impurities, and its chemical composition is as follows:
[0082] As can be seen from the above, in Comparative Example 2, iron and aluminum were precipitated directly by calcium oxide, but magnesium and calcium were not removed, and fluorine was not removed subsequently. The remaining impurity removal liquid still contained a large amount of metal ions, resulting in a high proportion of impurities in the final lithium phosphate. By using the deep impurity removal method of the present invention, the boron content in the final lithium phosphate in the above Examples 1-3 was reduced to less than 0.01%, and it basically did not contain impurities such as fluorine, calcium, and magnesium.
[0083] Comparative Example 3
[0084] Step 1: Weigh 1 kg of overhaul slag and pour it into a crusher for coarse crushing. Use a sealed sample making machine to grind it for 2-5 minutes until the particle size is less than 200 mesh slag powder 1. Its main chemical composition is as follows (elements are tested on a dry basis):
[0085] Step 2: Take 100g of slag powder 1, add it to 200mL of purified water, heat it to 85℃, stir it, add an appropriate amount of concentrated sulfuric acid, react for 4h, and maintain the pH value of the system at 2-2.5. Filter to obtain the crude electrolytic aluminum overhaul slag leaching liquid and leaching slag.
[0086] Step 3: The crude electrolytic aluminum overhaul slag leaching solution is heated to 60°C, an appropriate amount of hydrogen peroxide is added, sodium hydroxide is added to adjust the pH to 10-11, an appropriate amount of sodium carbonate is added to react for 1 hour, and filtered to obtain a primary impurity removal liquid. The chemical composition of the primary impurity removal liquid is as follows:
[0087] Step 4: Add the theoretical amount of sodium phosphate to the primary impurity removal solution in step 3 to precipitate lithium, to obtain lithium phosphate and lithium precipitation mother liquor. The lithium phosphate is washed with water and acid to remove impurities, and its chemical composition is as follows:
[0088] As can be seen from the above, in Comparative Example 2, the pH is directly adjusted to 10-11 by sodium hydroxide, which can precipitate iron, magnesium, calcium and aluminum ions, and the iron and aluminum precipitates exist in the system for a long time to absorb and take away lithium, but at the same time, when the alkalinity is enhanced, the aluminum hydroxide precipitate can also be dissolved, and the remaining impurity removal liquid still contains a large amount of metal ions, resulting in a high proportion of impurities in the final lithium phosphate. By using the deep impurity removal method of the present invention, the boron content in the final lithium phosphate in the above Examples 1-3 is reduced to less than 0.01%, and it basically does not contain impurities such as fluorine, calcium, and magnesium.
[0089] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0090] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0091] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution, characterized in that: The method comprises the following steps: Step 1, subjecting electrolytic aluminum overhaul slag to graded grinding to obtain slag powder with a preset particle size; Step 2, placing the slag powder in a corresponding container and adding pure water to mix and stir, then heating the water to 70-100° C., continuing to add strong acid to react for 2-4 hours to fully leach the lithium element, and filtering to obtain a crude electrolytic aluminum overhaul slag leachate and leach slag, wherein the strong acid is one of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid, and the pH value of the solution after adding the strong acid is 2-2.5, and the leachate contains iron and aluminum ions; Step 3, heating the crude electrolytic aluminum overhaul slag leaching solution obtained in step 2 to 50-70° C., then adding a preset amount of hydrogen peroxide to react, and adding a regulator to adjust the pH of the solution to 4-7, filtering to obtain a filtrate and iron-aluminum slag, wherein the regulator includes at least one of an alkaline salt and an alkaline oxide, and the filtrate contains calcium and magnesium ions; Step 4, adding a strong alkali solution to the filtrate obtained in step 3 to adjust the pH to 10-11, adding a strong base weak acid salt to react, filtering to obtain a primary impurity removal liquid and part of the calcium and magnesium slag, wherein the primary impurity removal liquid contains fluorine, and the molar amount of the strong base weak acid salt is 100-120% of the total molar amount of calcium and magnesium ions; Step 5, adding active magnesium oxide to the primary impurity removal liquid in step 4, stirring and reacting for a preset time at room temperature, so that the magnesium ions are hydrolyzed to form porous, highly dispersed, highly active hydroxides or hydrated oxides, and complexed with fluoride ions to form colloids or flocs, and filtered to obtain a secondary impurity removal liquid; Step 6, subjecting the secondary impurity removal liquid to metal ion adsorption treatment using an adsorption resin to obtain a tertiary impurity removal liquid; Step 7, adding a complexing agent for complexing with boron to the tertiary impurity removal solution, and adding a preset amount of sodium phosphate to obtain lithium phosphate and lithium precipitation mother liquor.
2. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 1, the overhaul slag is subjected to graded grinding treatment by first coarsely crushing the overhaul slag in a crusher and then grinding it using a sealed sample making machine. The D90 particle size of the slag powder obtained by the graded grinding treatment is less than or equal to 74 μm.
3. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 2, the mass volume ratio of slag powder to pure water is 1g: (2~5)mL.
4. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 3, the molar amount of hydrogen peroxide is 1 to 5 times the molar amount of iron in the leaching solution.
5. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 3, the alkaline salt includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate and potassium carbonate; the alkaline oxide includes at least one of calcium oxide and magnesium oxide.
6. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 4, the strong alkaline solution includes at least one of sodium hydroxide and potassium hydroxide, and the strong base weak acid salt includes at least one of sodium carbonate, sodium bicarbonate and potassium carbonate.
7. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 5, the mass of the active magnesium oxide is 30 to 100 times the mass of fluorine in the primary impurity removal liquid.
8. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 6, the adsorption resin includes at least one of aminophosphonic acid chelating resin, iminodiacetic acid resin and strongly acidic cation exchange resin.
9. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to claim 1, characterized in that: In step 7, the complexing agent includes one of N-methyl-D-glucamine, mannitol and glucose.
10. The method for deep impurity removal of electrolytic aluminum overhaul slag leaching solution according to any one of claims 1 to 9, characterized in that: In step 7, the molar amount of sodium phosphate added is (0.9-1.1) / 3 times the molar amount of lithium ions contained in the tertiary impurity removal solution.
Citation Information
Patent Citations
Preparation method of battery-grade lithium phosphate
CN111533100A
Production method for deeply removing fluorine from lithium sulfate solution
CN112250090A
Method for deeply removing fluorine from LiHCO3 solution recycled and leached from waste lithium batteries
CN112853120A
Method for recovering and preparing crude lithium carbonate from battery material raffinate
CN113582206A
Recycling treatment method for complex aluminum electrolyte
CN112342386A